Does carbohydrate supplementation maximize tennis match play performance? - Capitani, C. D.; Gomes, R. V.; Fernandez-Fernandez, J.; Mendez-Villanueva, A.; Moreira, A.; Aoki, M. S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The aim of the present study was to assess the effect of carbohydrate (CHO) supplementation on tennis match performance. Twelve young tennis players (18.0 ± 0.8 years) with national rankings among the top 50 in Brazil agreed to participate in the study. Methods: This study was conducted over a 5 day period in which each player completed 2 games of 3 hours simulated tennis match play either supplemented with a CHO or placebo (PLA) drinking solution. A randomized, cross-over, double blind research design was used. The activity profile of each match was determined by filming each match with two video cameras. Each player was individually tracked for the entire duration of the match. Two experienced researchers watched the matches and performed a match analysis. The following variables were calculated: (1) games won or lost; (2) rally duration (s); (3) strokes per rally; (4) rest time between rallies (s); (5) effective playing time (%); (6) changes of direction per rally; (7) aces; (8) double faults; (9) first service in; (10) second service in; (11) first return in and (12) second return in. Results: There were no between-condition differences in any of the variables analysed. Conclusion: In summary, the key finding of this study was that CHO supplementation did not improve tennis match play performance.